Pressure and temperature dependent dynamic flow and failure behavior of PMMA at intermediate strain rates - Zhang, L; Townsend, D; Petrinic, N; Pellegrino, A (Elsevier, 2021)
Polymethylmethacrylate (PMMA) has been widely used as transparency in aerospace and automobile engineering to enhance structural reliability under impact loading such as bird strike events. This study investigates the confined compressive behaviour of PMMA at quasi-static 0.01 s−1, medium rate 1-100 s−1 and intermediate strain rates 100-1000 s−1 from room temperature to elevated temperatures. Constant intermediate strain rate loading is achieved by using pulse shaping technique on a bespoke in-house developed split Hopkinson compression bar equipped with a high-speed camera and an environmental chamber. The material presents significant strain rate, temperature and pressure sensitivities. The failure mode at intermediate strain rate changes from brittle fragmentation without confinement to adiabatic shear banding with medium lateral confinement (65.3 MPa), which can be seen from the post-peak slope in the constitutive behavior, melting flow PMMA filaments observed in high speed photography and microstructural analysis. A series of intermediate strain rate experiments at elevated temperatures indicate that the higher temperature results in ductile failure for corresponding pressures. The temperature and strain rate dependent Drucker-Prager (DP) model is found to describe the response of PMMA. The brittle-ductile transition and pressure dependent model provide a better understanding of PMMA at intermediate strain rates, which is appropriate for engineering applications.